PENGARUH NET EKSPOR, KURS DOLLAR, dan INFLASI TERHADAP CADANGAN DEVISA INDONESIA PADA KURUN WAKTU TAHUN 1990-2016 - Tetry A., Sitohang; I Ketut, Sudiana (PIRAMIDA, 2019)
The aims of this study is to determine the effect of simultaneous, partial and the dominant influence between Net Export, Dollar Exchange Rate and Inflation of Indonesia's foreign exchange reserves. The data used in this study is secondary data period 1990-2016. Data analysis techniques used are multiple linear regression with the help of SPSS 16.00, equipped with the test of classical assumption and standardized coefficient beta. Based on the results of the test analysis, it can be concluded that (1) Simultaneously Net exports, dollar exchange rate, and Inflation have significant effect on Indonesia Foreign Exchange Reserve during 1990-2016 with sig value of 0.000. (2) Partially Net exports affect Indonesia's foreign exchange reserves during the period 1990-2016 with a beta coefficient of -2.042. (3) Partially, the dollar exchange rate has a positive and significant effect on Indonesia's Foreign Exchange Reserve for the period of 1990-2016 with a beta coefficient of 0.009. (4) Partially Inflation has no significant effect on Indonesia's Foreign Exchange Reserve of 1990-2016 with beta coefficient of -0.512. (5) The dollar is the most dominant variable with the beta coefficient of 0.926